Stereotactic body radiation therapy for metastasis in the lung: an undervalued treatment option with future prospects. (June 2012) - Song, Andrew; Shiue, Kevin; Machtay, Mitchell; Yao, Min; Ellis, Rodney J; Huang, Zhibin; Mayr, Nina A; Teh, Bin S; Lo, Simon S
SUMMARY The lung is a common site of metastatic disease from solid tumors. Most cancers can develop lung metastases, and sarcoma and epithelial (especially colorectal) malignancies are prone to metastasize to the lung. In particular, the International Registry of Lung Metastases describes 5206 cases of lung metastasectomy, of which 43% were epithelial and 42% were sarcomatoid. Common presenting symptoms include cough, hemoptysis, shortness of breath, chest pain and back pain. Data in the literature suggest the existence of an oligometastatic state, where metastases are limited in number and location. For selected patients with lung oligometastases, local therapy such as surgery, stereotactic body radiotherapy (SBRT) and radiofrequency ablation may potentially yield prolonged survival. Data from retrospective series and prospective trials on the use of SBRT for lung metastases are emerging, showing promising results. Most studies show high local control rates rivaling those found in studies of surgical management (the usual treatment of choice) for lung metastases, while SBRT also has the benefit of low rates of significant toxicities. This review will provide an overview of the utilization of SBRT in the management of lung oligometastases.